2003
DOI: 10.1189/jlb.0103035
|View full text |Cite
|
Sign up to set email alerts
|

The role of TNF–TNFR2 interactions in generation of CTL responses and clearance of hepatic adenovirus infection

Abstract: Deficiency or inhibition of tumor necrosis factor (TNF) significantly prolongs hepatic expression of recombinant adenoviral vectors. To explore mechanisms responsible for this observation, the present studies examined the effects of TNF versus TNF receptor 1 (TNFR1) or TNFR2 deficiency on the course of antiviral-immune responses to a replication-deficient, beta-galactosidase-encoding recombinant adenovirus (AdCMV-lacZ). Clearance of AdCMV-lacZ was significantly delayed in TNF-deficient mice. Less pronounced bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…A study by another group confirmed that TNFR2 functioned as a costimulator for human T cells (22). Another study found that TNFR2 Ϫ/Ϫ mice display delayed clearance of replication-deficient adenovirus that correlated with decreased adenovirus-specific CTL activity of intrahepatic lymphocytes, indicating that TNFR2 facilitates generation of CTL effector function for antiviral immune responses in the liver in vivo (23). These studies indicate that TNFR2 functions in T cells as an important costimulator for the differentiation program triggered by TCR-mediated stimulation.…”
mentioning
confidence: 78%
“…A study by another group confirmed that TNFR2 functioned as a costimulator for human T cells (22). Another study found that TNFR2 Ϫ/Ϫ mice display delayed clearance of replication-deficient adenovirus that correlated with decreased adenovirus-specific CTL activity of intrahepatic lymphocytes, indicating that TNFR2 facilitates generation of CTL effector function for antiviral immune responses in the liver in vivo (23). These studies indicate that TNFR2 functions in T cells as an important costimulator for the differentiation program triggered by TCR-mediated stimulation.…”
mentioning
confidence: 78%
“…␤-Galactosidase activity in liver tissue homogenates was quantified by measuring the rate of cleavage of 4-methylumbelliferyl-␤-D-galactoside to yield the fluorescent product 4-methylumbelliferone as previously described. 20,24 For each sample, the reported value is an average of dilutions falling in the assay linear range.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, marked delay in hepatic adenoviral infection is noted in mice deficient in Fas, FasL, or TNF expression. 13,20,[23][24][25] However, mice with isolated defects in expression of TNFR1, the major mediator of TNF-induced apoptosis, clear hepatic adenoviral infection at rates similar to those in wild-type mice, whereas mice with defects in either TNF or tumor necrosis factor receptor 2 expression exhibit delays in adenoviral clearance that seem to be related to diminished activation of intrahepatic FasL-expressing CTL. 24 Thus, results of prior studies suggest that among the various CTL effector pathways, FasL/Fas-mediated cytotoxic effector mechanisms play the most prominent role in clearance of hepatic viral infections, 20,24 whereas the potential role of other cytotoxic effector mechanisms remains unclear.…”
mentioning
confidence: 99%
“…Human PBMC, human Huh-7 hepatoma cells (22), and mouse AML-12 cells (23) were cultured in 25 cm 2 tissue culture flasks (Costar, Cambridge, MA) at 37°C in a humidified, 5% CO 2 atmosphere in RPMI 1640 medium (Huh-7 cells; BioWhittaker, Walkersville, MD) or equal proportions of DMEM and F12 medium (AML-12 cells; BioWhittaker), supplemented with 10% FBS (Life Technologies, Gaithersburg, MD), 1 mM pyruvate, 100 g/ml streptomycin, and 200 U/ml penicillin G. PBMC cultures were supplemented with 0.5 g/ml PHA (Roche Molecular Biochemicals, Indianapolis, IN) for 3 days to activate T lymphocytes or with 100 U/ml rIL-2 for 2 days to generate lymphokine-activated killer (LAK) cells. Anti-H-2 q -specific CTL were generated in 5-day MLC containing 12 ϫ 10 6 responder spleen cells from C57BL/6 background (H-2 b ) mice and equal numbers of irradiated FVB-NJ (H-2 q ) stimulator spleen cells in 6 ml of RPMI 1640 medium supplemented with 10% FBS as previously described (10,12).…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%